THE CORRELATION BETWEEN EFL READING MOTIVATION AND READING COMPREHENSION ABILITY - Elvina Hartono (Widya Mandala Surabaya Catholic University, 2016)
This study examined to describe the correlation between EFL students’ reading motivation and their reading comprehension ability. The six dimensions from the Motivation for Reading Questionnaire were used to examine students’ motivation. The modified Questionnaire and a reading comprehension test were distributed to forty five grade twelve students in a private school in Surabaya. The Pearson correlation and multiple regression analysis were conducted to answer the research question. The correlation between students; reading motivations and their reading comprehension ability was 0.321. Thus the correlation between students’ reading comprehension was positive but low.